Palliative Care Intervention in the Intensive Care Unit: Comparing Outcomes among Seriously Ill Asian Patients and those of Other Ethnicities. Issue 3 (September 2014) - Gutierrez, Cristina; Hsu, William; Ouyang, Qin; Yao, Haijun; Pollack, Simcha; Pan, Cynthia X.
Background: The literature describing the attitude of Asians toward palliative care in the intensive care unit (ICU) is scarce. Aim: The purpose of this study was to compare outcomes of Asians and people of other ethnicities after palliative care intervention in the ICU. Methods: A retrospective chart review was conducted of all ICU patients evaluated by palliative care; the outcomes measured were incidence of life-sustaining treatments, institution of advance care directives, and preferences for end-of-life care. Results: The palliative care team evaluated 119 patients (46.2 percent Caucasian, 27.2 percent Asian, and 26.1 percent other ethnicities). There were no differences in demographics or clinical variables. Thirty-six percent of the Asians, 49 percent of the Caucasians, and 28.6 percent of the patients of other ethnicities (p=0.19) had healthcare proxies. The palliative care team increased advance care directives by more than 40 percent in all groups (p<0.001). There were no differences in the use of life-sustaining treatments or preferences for comfort measures among ethnic groups. Conclusion: Asians are as likely as people of other ethnicities to decide on advance care directives, life-sustaining treatments, and comfort measures after palliative care evaluation in the ICU. Contexte: Il existe très peu de publications décrivant l'attitude des asiatiques envers l'intervention des spécialistes en soins palliatifs dans le service de soins intensifs. But: Cette étude avait pour but de comparer les résultats obtenus chez les asiatiques et d'autres groupes ethniques après l'intervention de ces spécialistes auprès des patients et de leur famille dans le service de soins intensifs. Méthode: On a fait l'analyse rétrospective des dossiers de tous les patients ayant été rencontrés par l'équipe de soins palliatifs; les résultats de l'analyse portaient sur la fréquence des traitements de prolongation de vie, les directives de fin de vie, et les préférences des patients en ce qui avait trait aux soins de fin de vie. Résultats: L'équipe de soins palliatifs a évalué les dossiers de 119 patients (46, 2 pourcent d'origine caucasienne, 27, 2 pourcent d'origine asiatique, et 26, 1 pourcent de diverses origines). Trente-six pourcent des asiatiques, 49 pourcent des caucasiens, et 28, 6 pourcent des autres ethniques (p=19) avaient déjà choisi leur mandataire légal. L'équipe de soins palliatifs a augmenté le recours aux directives de fin de vie par plus de 40 pourcent dans tous les groupes (p=<0, 001). Il n'y avait aucune différence entre ces groupes quant au recours aux traitements de fin de vie et aux mesures de confort du patient. Conclusion: Suite à une rencontre avec l'équipe de soins palliatifs, les asiatiques, tout comme les autres groupes ethniques, sont tout autant susceptibles de décider de leurs traitements de fin de vie et de recourir aux mesures de confort et aux directives préalables.